Crohn's disease presenting as acute abdomen diagnosis and management a Case Report (Journal of Surgical Sciences, 2019)
CD is characterised by a chronic full thickness inflammatory process that can affect any part ofthe gastrointestinal tract from the lips to the anal margin. We present a case of acute abdomenadmitted in CMH Rangpur. Exploratory laparotomy was performed and diseased resectedsegments were confirmed as Crohn's Disease on histopathology.Journal of Surgical Sciences (2017) Vol. 21 (1) :36-38